The role of interpretation of the law in the mechanism of bridging gaps in the law - Matat, Yurii I.; Матат, Юрій Ігорович; Matat, Yu. I.; Матат, Ю. І.; Матат, Юрий Игоревич (Одеса : Гельветика, 2020)
The article is devoted to the study of the legal nature of the interpretation of law, its features, as well as the role in overcoming gaps in the law. Attention is focused and substantiated that the interpretation of legal norms, being a necessary element of the legal regulation mechanism, plays the important role in the process of overcoming gaps in law. So, by means of various methods of interpretation, in particular, formal gaps are overcome, which, in turn, may arise as a result of an unsuccessful presentation of legal norms by the legislator. It is determined that when applying the rule of law by analogy, such a rule in the particular situation should be interpreted not as part of the institution from which it is borrowed, but as part of the institution, the gap in which it is designed to overcome. This is due to the fact that the rule applied by analogy is subject to double influence: on the one hand, it generally retains its original meaning, on the other – partially adapts to the characteristics of the institution in which the gap is overcome through it.The role of official interpretation in the process of application of the law in the conditions of gaps in the legislation is clarified, the role of recommendatory explanations provided by higher courts on the issues of application of the legislation is investigated. In Ukraine, these powers, in accordance with the Law of Ukraine “On the Judicial System and the Status of Judges” dated June 02, 2016, are assigned to the Plenum of the Supreme Court, in order to ensure the same application of the rules of law in solving certain categories of cases, generalizes the practice of applying substantive and procedural laws, systematizes and ensures the promulgation legal positions of the Supreme Court, as well as based on the results of the analysis of judicial statistics and generalization of judicial practice, it provides explanations of the recommendatory nature on the application of legislation in solving court cases.It is concluded that the importance of the interpretation of law is primarily to ensure full and accurate disclosure of the functions of legal acts as a source and form of existence of legal norms, other substantive elements of the legal system. The interpretation concretizes the law, which allows law enforcement agencies to ensure the resolution of legal cases in strict accordance with the constitutional principles of legal certainty, legality and the rule of law.

Стаття присвячена дослідженню юридичної природи тлумачення права, його особливостей, а також ролі в процесі подолання прогалин у законодавстві. Акцентується увага та обґрунтовується, що тлумачення норм права, будучи необхідним елементом механізму правового регулювання, відіграє важливу роль у процесі подолання прогалин у законодавстві. Так, за посередництвом різних способів тлумачення долаються, зокрема, формальні прогалини, які у свою чергу можуть виникати внаслідок невдалого викладення законодавцем правових норм. Визначено, що в разі застосування норми права за аналогією така норма в конкретній ситуації має тлумачитися не як частина інституту, з якого її запозичено, а як складник інституту, прогалину в якому вона покликана подолати. Указане пов’язано з тим, що норма, застосовувана за аналогією, піддається подвійному впливу: з одного боку, вона в цілому зберігає первинний смисл, з другого – частково пристосовується до особливостей того інституту, прогалина в якому долається за її посередництвом. З’ясовано роль офіційного тлумачення в процесі застосування права в умовах прогалин у законодавстві, досліджено роль рекомендаційних роз’яснень, що надаються вищими судами, з питань застосування законодавства. В Україні зазначені повноваження згідно із Законом України «Про судоустрій і статус суддів» від 02.06.2016 р. покладено на Пленум Верховного Суду, який з метою забезпечення однакового застосування норм права під час вирішення окремих категорій справ узагальнює практику застосування матеріального і процесуального законів, систематизує та забезпечує оприлюднення правових позицій Верховного Суду, а також за результатами аналізу судової статистики та узагальнення судової практики надає роз’яснення рекомендаційного характеру з питань застосування законодавства у вирішенні судових справ. Зроблено висновок, що значення тлумачення права полягає насамперед у забезпеченні повного й точного розкриття функцій правових актів як джерела й форми існування юридичних норм, інших змістовних елементів правової системи. За допомогою тлумачення здійснюється конкретизація права, яка дає змогу правозастосовним органам забезпечити вирішення юридичних справ у суворій відповідності конституційним принципам правової визначеності, законності й верховенства права.

Статья посвящена исследованию юридической природы толкования права, его особенностей, а также роли в процессе преодоления пробелов в законодательстве. Акцентируется внимание и обосновывается, что толкование норм права, являясь необходимым элементом механизма правового регулирования, играет важную роль в процессе преодоления пробелов в законодательстве. Так, посредством различных способов толкования преодолеваются, в частности, формальные пробелы, которые в свою очередь могут возникать вследствие неудачного изложения законодателем правовых норм. Определено, что в случае применения нормы права по аналогии такая норма в конкретной ситуации должно толковаться не как часть института, из которого она заимствована, а как составляющая института, пробел в котором она призвана преодолеть. Указанное связано с тем, что норма, применяемая по аналогии, подвергается двойному воздействию: с одной стороны, она в целом сохраняет первоначальный смысл, а с другой - частично приспосабливается к особенностям того института, пробел в котором преодолевается за ее посредничестве. Выяснена роль официального толкования в процессе применения права в условиях пробелов в законодательстве, исследована роль рекомендательных разъяснений, предоставляемых высшими судами, по вопросам применения законодательства. В Украине указанные полномочия в соответствии с Законом Украины «О судоустройстве и статусе судей» от 02.06.2016 г.. Возложено на Пленум Верховного Суда, с целью обеспечения одинакового применения норм права при решении отдельных категорий дел обобщает практику применения материального и процессуального законов, систематизирует и обеспечивает обнародования правовых позиций Верховного Суда, а также по результатам анализа судебной статистики и обобщения судебной практики дает разъяснения рекомендательного характера по вопросам применения законодательства в решении судебных дел. Сделан вывод, что значение толкования права заключается прежде всего в обеспечении полного и точного раскрытия функций правовых актов как источника и формы существования юридических норм, других содержательных элементов правовой системы. С помощью толкование осуществляется конкретизация права, которая позволяет правоприменительным органам обеспечить решение юридических дел в строгом соответствии конституционным принципам правовой определенности, законности и верховенства права.
Matat Yu. I. The role of interpretation of the law in the mechanism of bridging gaps in the law / Yu. I. Matat // Актуальні проблеми держави і права : зб. наук. пр. Вип. 87 / редкол.: Г. I. Чанишева (голов. ред.) та ін. – Одеса : Гельветика, 2020. – С. 107-112.
Keywords: тлумачення права; прогалини в законодавстві; правозастосування; добудова (розвиток) права; судова правотворчість; interpretation of law; gaps in law; law enforcement; completion (development) of law; judicial lawmaking; толкования права; пробелы в законодательстве; правоприменение; достройка (развитие) права; судебное правотворчество; Research Subject Categories::LAW/JURISPRUDENCE